Обгрунтування комплексу антиоксидантів для стабілізації косметичного крему - Марченко, Валерія Сергіївна; Кричковська, Лідія Василівна; Бєлінська, Анна Павлівна (НТУ "ХПІ", 2015)
У статті запропоновано комплекс антиоксидантів для захисту від окиснювального псування косметичного крему, збагаченого на ω-3 поліненасичені жирні кислоти. Визначено залежність періоду індукції окиснення жирової основи косметичного крему від вмісту і співвідношення обраних антиоксидантів. Обґрунтовано співвідношення антиоксидантів та їх дозування у складі косметичного продукту.

One of the perspective directions of cosmetics production is to create products with highly active substances for dry, aging, prone to irritations skin. This paper proposes a complex of antioxidants to protect a cosmetic cream, enriched with ω-3 polyunsaturated fatty acids, against oxidative damage. The dependence of the induction period of fat base oxidation of the cosmetic cream on the content and the ratio of selected antioxidants is defined. The ratio and dosage of antioxidants – retinol, tocopherol, thiotriazoline – have been substantiated to be used as the cosmetic cream compounds. Their mutual influence on inhibition of oxidative damage of cream triacylglycerol fat basis is found. Development of the cosmetic product enriched ω-3 PUFA with selected antioxidants will allow to increase shelf life of products, and thereby improve the competitive position of national producers in the industry.
Substantiation of a combination of antioxidants for cosmetic creams
Keywords: виробництво косметичних засобів; косметичний крем; антиоксиданти; ретинол; поліненасичені жирні кислоти; купажована олія; antioxidants; cosmetic cream; polyunsaturated fatty acids; blended oil